DYNAMICS OF MANUFACTURING OF AN AGRICULTURAL PRODUCTION WITH EXCESS OF PERMISSIBLE LEVELS OF 137CS AND 90SR CONCENTRATION IN BELARUS - N. N. Tsybulko (Радиационная гигиена)
The analysis of the volumes of manufacturing in Belarus of an agricultural production with excess of permissible levels of 137Cs and 90Sr concentration for the period which has passed after failure on the Chernobyl NPP is carried out. It is shown, that from all kinds of production which is not meeting standard requirements for the radionuclides concentration, the majority falls on the grain unsuitable for the food purposes due to 90Sr concentration. Annually, it is registered from 25 to 55 thousand tons of such grain. In considerable volumes forages, with specific 137Cs and 90Sr activity, exceeding republican permissible levels are also produced. whole do not exceed total exposure doses for the inhabitants of Krasnoyarsk region.